Flavonoids Docked into Several Target Proteins Associated with Cancer: A Molecular Docking Study - Mohd F. A. Ghani; Noraziah Nordin; Nazefah Abdul Hamid (Faculty of Pharmacy, University of Benin, 2024)
Indexed by Scopus